Management of Urban Air Quality: Evaluating the Sequestration Potential of Green Infrastructure Against Domestic Transportation Emissions - Muhammad Mahfuzh Huda; Susana Elmira Uba Lamadoken; Wahyu Atiq Widiantoro; Dwi Fitrianingsih; Raely Harza Wiltianza Wiltianza (Tecno Scientifica Publishing, 2026)
Rapid urbanization escalated domestic vehicular CO₂ emissions, necessitating the optimization of urban green open spaces (GOS) as engineered biological sinks. However, urban planning practices frequently prioritized spatial area over species-specific sequestration capacity, leading to potential spatial inefficiencies. This study evaluated the efficacy of four GOS in Tanjung Redeb, Indonesia, by overlaying localized vehicular emission loads—calculated using the Vehicle Kilometer Traveled (VKT) model—with the biological sequestration capacities of the parks, quantified through species-specific allometric equations. The results indicated that all evaluated parks operated at a net positive carbon surplus, with absorption ratios ranging from 1,474.8% to 117,668.6%. Crucially, the empirical data exposed a severe source–sink decoupling. The primary emission hotspot, Taman Bukit Maritam (1,032.33 kg CO₂/year), relied on moderately performing vegetation, yielding the lowest relative surplus. Conversely, the highest sequestration capacity (37,010.96 kg CO₂/year) was located in Taman Sanggam, a low-stress corridor (92.33 kg CO₂/year), driven by the aggressive structural biomass of the hyper-accumulator Samanea saman. The analysis demonstrated that biological filtration performance was strictly dictated by species taxonomy and allometric structure, rather than stand age or total park area. The study concluded that mitigating urban vehicular emissions required a paradigm shift from passive aesthetic landscaping to active, data-driven biological engineering, deploying high-capacity hyper-accumulators strategically along high-emission transportation corridors.